Hammered Dulcimer - Williams, Lisa (Utah State University, University Libraries, 1998)
May Swenson Poetry Award Volume 2, with foreward by John Hollander. Lisa William's poems are infused with what John Hollander calls ""a guarded wonder."" A poet of unique vision, she seems always to be ""looking at,"" with special attention to the experience of the senses. Moreover, Williams is equally concerned with epistemology